Efficacy of protracted dose-dense temozolomide in patients with recurrent high-grade glioma - ATASOY, BESTE MELEK; YUMUK, PERRAN FULDEN (SPRINGER, 2011)
The current standard therapy for newly diagnosed glioblastoma is multimodal, comprising surgical resection plus radiotherapy and concurrent temozolomide, then adjuvant temozolomide for 6 months. This has been shown to provide survival benefits; however, the prognosis for these patients remains poor, and most relapse. The objective of this prospective Phase II study was to evaluate the efficacy and tolerability of protracted, dose-dense temozolomide therapy (100 mg/m(2) for 21 consecutive days of a 28-day cycle) in patients with recurrent glioblastoma or grade 3 gliomas who had previously received standard therapy. Of the 25 patients included (median age 50 years), 20 were evaluable for radiologic response. Two patients had partial responses and 10 had stable disease (60% overall clinical benefit); 8 patients (40%) progressed after the first treatment cycle. Five patients were not assessed for radiologic response due to early clinical progression but were included in the progression-free survival (PFS) and overall survival (OS) analyses. The median follow-up time was 7 months (range, 1-14 months). The median PFS was 3 months (95% confidence interval, CI, 1.8-4.2) and the median OS was 7 months (95% CI 5.1-8.9). The 6-month PFS rate (primary endpoint) was 17.3% (95% CI 1.7-32.2) and the 1-year OS rate was 12% (95% CI -1-25). This regimen was well tolerated. The most frequent adverse event was lymphopenia (grade 3-4 in 20 patients); no opportunistic infections were reported. Treatment was discontinued due to toxicity in 2 patients (grade 4 hepatic toxicity and thrombocytopenia). These data suggest that protracted, dose-dense temozolomide had modest activity with manageable toxicity in patients with recurrent high-grade glioma previously treated with temozolomide.
Keywords: Protracted; Temozolomide; High-grade glioma; Glioblastoma; PHASE-II TRIAL; BEVACIZUMAB PLUS IRINOTECAN; NEWLY-DIAGNOSED GLIOBLASTOMA; NEURO-ONCOLOGIA GICNO; MALIGNANT GLIOMA; ANTITUMOR IMIDAZOTETRAZINES; 1ST RELAPSE; O-6-ALKYLGUANINE-DNA ALKYLTRANSFERASE; ANAPLASTIC ASTROCYTOMA; ADJUVANT TEMOZOLOMIDE